HUBUNGAN PREFERENSI PEMILIHAN PASANGAN HIDUP DENGAN KECEMASAN TERHADAP PERNIKAHAN PADA GEN-Z - Alghifari, Kamila Nur Fatimah; Khairyasdien , Andhita Dyorita (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Anxiety about marriage in Gen-Z is influenced by various things, one of which is social environmental factors, Gen-Z has not found a life partner that fits the desired criteria. The purpose of this study is to reveal the relationship between preferences in choosing a life partner and anxiety about marriage in Gen-Z. The approach used in this study is quantitative correlation with purposive sampling technique. The sample size is 134 respondents from Gen-Z with an age range of 20-34 years in Bandung Regency. Data was obtained through a scale that measures the value of Anxiety about marriage and preferences in choosing a life partner. The results of the research analysis show a positive relationship with a value of 0.210 and a significance of 0.15 (p <0.05), with the assumption that the higher the preference for choosing a life partner, the higher the anxiety about marriage. Conversely, if the preference for choosing a life partner is lower, the anxiety about marriage is lower. Keyword : Anxiety about marriage, choice of partner preference, Generation-Z